Control of Fully Actuated Mechanical Systems via Super-twisting Based Lyapunov Redesign. Issue 2 (2020) - Estrada, Manuel A.; Fridman, Leonid; Moreno, Jaime A.
Abstract: The problem control of fully actuated of mechanical systems under uncertainties is considered. With this aim a concept of Lyapunov redesign is revisited. The derivative of the Lyapunov function for a nominal model of the robot is used for the sliding surface design. This surface permits to design a super-twisting controller allowing to compensate the Lipschitz uncertainties, providing theoretically exact convergence of the states of uncertain system to the origin by means of a continuous control signal. The proposed result is illustrated for simulation example controlling an uncertain planar robot.